Sinking or swimming in the cluster labor pool? A firm-specific analysis of the effect of specialized labour - Nils Grashof (Friedrich Schiller University Jena, 2020)
Human resources are a key factor for firm success, particularly nowadays when most industrial economies face an increasing shortage of qualified labour. With their pooled labour markets, regional clusters have been shown to be a preferable location for firms in order to satisfy their demand for skilled employees. Nevertheless, in light of possible disadvantages (e.g. labour poaching) and the broad field of studies dealing with firm performance differentials, the prevalent assumption that all companies profit equally from the specialized labour pool in clusters must be questioned. Consequently, the aim of this paper is to empirically investigate the conditions and mechanisms through which companies located in clusters can gain, in terms of innovativeness, from the specialized labour pool. By synthesizing theoretical streams from the strategic management (e.g. resource-based view) and the economic geography literature (e.g. cluster approach), variables from three different levels of analysis (micro-level, meso-level and macro-level) are examined separately as well as interactively. Apart from revealing that being located in a cluster indeed increases on average firm innovativeness, one of the central findings is that firms benefit unequally within the cluster environment depending on the specific firm-level, cluster-level, industry-/market-level conditions and their respective interactions.
Keywords: C31; J24; L22; O30; R10; R23; 330; specialized labour pool; cluster; agglomeration; firm performance differentials; innovation